Balinese Local Wisdom Oriented Digital Teaching Materials to Improve Cultural Literacy of Grade V Elementary School Students - Udiyana, I Gede; Arnyana , Ida Bagus Putu (Journal for Lesson and Learning Studies, 2022)
The integration of local wisdom in learning is still lacking. Teachers are still not able to integrate local wisdom into learning. This study aims to create digital teaching materials oriented to Balinese local wisdom for fifth grade elementary school. This research is development research with ADDIE model. Data is classified into two, namely qualitative data and quantitative data. Data collection techniques using a questionnaire technique. Questionnaires were used to measure the validity and practicality of digital teaching materials. Validity was tested by two experts, namely material experts, media experts, and design experts. Practicality was assessed by 8 teachers and 8 fifth grade elementary school students. The data were analyzed descriptively quantitatively. The results of this study indicate that the analysis of the validity test shows that the overall average validation is 3.84 and is in the very valid category. The practicality of these digital teaching materials shows that the average teacher assessment of the practicality of digital teaching materials is 3.78 and is in the very practical category. The student's assessment was obtained at 3.65 which was in the very practical category. The t-test shows that the value of Sig.(2-tailed) <0.05 is significant. So, digital teaching materials oriented to Balinese local wisdom to improve students' cultural literacy on the Ecosystem material for grade V elementary school which is very valid, very practical, and effective.